The effectiveness of pre-performance routines in sports: a meta-analysis - Rupprecht, A. G. O.; Tran, U. S.; Gröpel, P. (International Review of Sport and Exercise Psychology, 2024)
A pre-performance routine (PPR) refers to a set of task-relevant thoughts and actions an athlete systematically engages in prior to performance execution. The aim of this meta-analysis was to determine the effectiveness of the PPR intervention to facilitate sport performance. The meta-analysis included 112 effect sizes from pre-post and experimental designs in low-pressure and pressurised conditions. Extensive PPRs with several preparatory elements as well as specific stand-alone PPRs, such as left-hand dynamic handgrip and quiet eye, were analysed. Three-level random-effects models were used for analysis, utilising Knapp-Hartung adjustments and restricted maximum likelihood estimation. Results showed a significant but small effect of PPRs on sport performance in pre-post designs (SMC = 0.31, 95% CI [0.18, 0.44]) and moderate-to-large effects in experimental designs, both under low-pressure (Hedges` g = 0.64, 95% CI [0.45, 0.83]) and pressurised conditions (Hedges` g = 0.70, 95% CI [0.24, 1.16]). These effects were not moderated by the type of PPR, age, gender, skill level, or intervention characteristics. Overall, the meta-analytic results support the benefits of the PPR intervention in practice regardless of the type of routine. Both extensive and stand-alone PPRs are effective in optimising sport performance.